IMPACT OF INDIVIDUALS SAVING AND CONSUMPTION BEHAVIOUR TOWARDS INVESTMENT AS INFLOW OF MONEY IN THE ECONOMY OF PAKISTAN : A CASE OF SALARIED CLASS - Waqar, Munir; Jerome, Kueh; Muhammad Asraf, Abdullah (AESS Publications, 2022)
Savings and consumption are the central core valuable factors in the growth of an economy. Saving and investment are specifically crucial for individuals and the government for smooth economic growth and wellbeing of the peoples. This study has used the federal government salaried class individuals with the convenience sampling of 550 participants including both male and female. The theory of permanent income study and lifecycle hypothesis support the consumption and savings patterns of the salaried class with their retirement planning and investment decisions. These decisions are also affected by the living standards and investment scams prevailing in the market. The Structural Equation Modelling-Partial Least Square (SEM-PLS) method is used in this study. The literature results revealed that saving patters and consumption patterns significantly impact investment decision of individuals. The moderating role of living standards and the mediating role of retirement planning on investment and savings relationships is essential in today's era for the better investment decision and as inflow of money in the economy. This study will help the policy makers and government to define the policies and regulations for the save investment avenues. However, the model has not been tested empirically, but the literature and study hypothesis support the model and study hypothesis. A future empirical study can be carried on using this model.